Surface oxidation-induced restructuring of liquid Pd–Ga SCALMS model catalysts. Issue 30 (27th July 2021) - Wittkämper, Haiko; Maisel, Sven; Moritz, Michael; Grabau, Mathias; Görling, Andreas; Steinrück, Hans-Peter; Papp, Christian
Abstract : We have examined model systems for the recently reported Pd–Ga Supported Catalytically Active Liquid Metal Solutions (SCALMS) catalysts using near-ambient pressure X-ray photoelectron spectroscopy (NAP-XPS) under oxidizing conditions. Abstract : We have examined model systems for the recently reported Pd–Ga Supported Catalytically Active Liquid Metal Solutions (SCALMS) catalysts using near-ambient pressure X-ray photoelectron spectroscopy (NAP-XPS) under oxidizing conditions. Gallium is known to be highly prone to oxidation and in practical applications, handling of the catalyst material in air or the presence of traces of oxygen in the reactor are unavoidable. Therefore, we expect our results to be of high relevance for the application of Ga-based SCALMS catalysts. Pd–Ga alloy samples of 1.3 and 1.8 at% Pd content were exposed to molecular oxygen at different pressures between 3 × 10 −7 and 1 mbar and a temperature of 550 K. We observe the formation of wetting Ga2 O3 films upon exposure to molecular oxygen. The absolute thicknesses of the oxide films depend on oxygen pressure, with values ranging from ∼12 Å at 10 −7 to 10 −5 mbar to ∼50 Å at 1 mbar. The formed metal-oxide interface leads to a redistribution of Pd, which accumulates at the boundary between the wetting oxide film and the metal substrate as a response to the oxide film growth. A maximum Pd 3d intensity is observed at an oxide thickness of 5 Å. For thicker films, the Pd 3d signal and the Ga 3d signal ascribed to the metallic substrate decrease in parallel, which is attributed to the oxide layer growing on top of the liquid metal alloy. From this observation, we conclude that no significant amount of Pd is bound in the newly formed oxide film. Density-functional theory (DFT) calculations support the experimental observations.